PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN INDRAGIRI HULU - Muhammad Nobel Darmansyah; Restu Agusti; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Budget (budget) is based approach to performance, which is a budget system that promotes the achievement of the work or the output of the cost allocation plan or the specified input. Based approach to performance, budgets prepared to be at a certain target to be achieved in one fiscal year. The purpose and this study was to examine the effect on the performance characteristics of the budget objectives of local government officials in IndragiriHulu.The population in this study is that local government officials under the Regional Secretary Indragiri Hulu, namely offices located in Indragiri Hulu, amounting to 15 offices and a total sample of 60 respondents. The sampling technique in this research is purposive sampling technique to sample the selection of certain considerations, these considerations are based on interests or research objectives of this study was to test the hypothesis using multiple linear regression analysis. The independent variable in this study is the participation of the budget, the budget goal clarity, feedback budgets, budget evaluation, and difficulty budgetary purposes. While the dependent variable is the performance of local government officials. Based on the results of the calculation of the value of coefficient of determination (R2) obtained value of R Square of 0532. This shows that the influence of the independent variables simultaneously on the dependent variable is equal to 53.2%, while the remaining 46.8% is influenced by other variables that are not included in this study. Hypothesis testing results show that the variable budget participation, feedback budgets, budget evaluation, and difficulty budgetary purposes signikan effect on performance variables. While the budget goal clarity variables no significant effect on performance variables.Keywords: Participation budget, budget goal clarity, feedback budgets, budget evaluation, difficulty budgetary purposes, the performance of local government officials.